Comparative efficacy of drug-eluting balloon and drug-eluting stent for treatment of in-stent restenosis: a systematic review and meta-analysis - Tinanda Tarigan; Daniel Sukmadja; Kaka Citta Prasiddha; Rizkan Triatmaja (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the efficacy of drug-eluting stents and drug-eluting balloons in treating in-stent restenosis. Method: The systematic review was conducted from January to February 2022, and comprised literature search on PubMed, ProQuest, Cochrane Library and Google Scholar databases with relevant key words to locate randomised controlled trials and observational studies published between 2000 and 2022 that compared drugeluting balloons and drug-eluting stents in the treatment of in-stent restenosis. The outcomes were all-cause death, cardiovascular death, major adverse cardiovascular events, myocardial infarction, stent thrombosis, stroke and target vessel revascularisation. The pooled risk ratio for each outcome was analysed. Data was analysed using Review Manager 5.1. Results: Of the 1,105 studies identified, 11(0.99%) were analysed in detail; 7(63.6%) randomised controlled trials and 4(36.4%) observational studies. There were 2,437 patients with in-stent restenosis. There was no significant difference between drug-eluting balloons and drugeluting stents with respect to all-cause death, cardiovascular death, stroke, stent thrombosis, myocardial infarction and major adverse cardiovascular events (p>0.05). Drug-eluting stents significantly caused more target vessel revascularisation compared to drugeluting balloons (p=0.004). Conclusions: Except for target vessel revascularisation, the drug-eluting balloons and drug-eluting stents had no difference in terms of clinical outcomes related to in-stent restenosis patients. Key Words: Eluting stents, Coronary restenosis, Myocardial infarction, Thrombosis.